Analisis peranan dan daya saing sector pertanian serta pengaruhnya terhadap pertumbuhan ekonomi Kabupaten Muaro Jambi - Maranata Maranata; Erfit Erfit; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
The purpose of this study was to analyze the role of the agricultural sector in Muaro Jambi Regency, to analyze the level of competitiveness of the agricultural sector in Muaro Jambi Regency, and to analyze the influence of agricultural sector labor on economic growth in Muaro Jambi Regency during the 2001-2015 period. This study uses descriptive and quantitative analysis methods. The results of the analysis show that the agricultural sector can provide a large role for the economy in Muaro Jambi Regency and become the base or leading sector during the 2001-2015 period with an average LQ value of 1.17. The shift-share analysis shows that the agricultural sector has a very high regional growth value, fast proportional growth, and regional share growth that is competitive compared to other sectors in other regions during the 2001-2015 period. Agricultural sector workers have a positive and significant effect on economic growth in Muaro Jambi Regency. Keywords: Agricultural sector, Base sector, Competitiveness, Labor, Economic growth